Sociological Study About the Issues of Women Career Advancement at Male-Dominated Workplace - Shabana Muhammad Anwar; Anam Aqil Khan; Palwasha Ain-ud-din (Journal of Management Practices, Humanities and Social Sciences, 2021)
Extensive studies have been conducted to focus on the obstacles of women's career advancement in organizations. Still, scarce literature exists related to women's career advancement in the tribal system of Pakistan. The purpose of this article is to reveal hinders of women's career advancement in a male's subjugated work environment. Statistics of current research disclose gender preference exists related to the career advancement of employees in organizations. Women in the workforce remain undervalued as compared to male workers. Gender disparity appears in career development based on age, education, traditional values, ethnicity, preference of male workers. Equal opportunities for both gender for career advancement play a significant role in progression. Several studies have been conducted related to issues of women's career advancement but, in the context of the tribal system of Balochistan little studies have been conducted. Therefore, a researcher is interested in highlighting the issues of women's career advancement, especially in the tribal system of Balochistan. The quantitative study was designed to achieve the objectives of the research. The information was collected from the universe composed of higher educational institutes and directorates of Quetta (Balochistan). The simple random sampling technique was used to select 500 female employees for the purpose of data gathering. A structured questionnaire was distributed, generated a hypothetical statement through previous literature was tested by SPSS. The result of the conducted study shows that organizations give more power, prestige and authority to men than women to achieve their professional goals smoothly. Women in the workplace do not have equal opportunities for career development; they have fewer chances of participation in different specialized pieces of training and workshops which enhance their professional growth. The male staff has more stable paths of career development in the male-dominated workplace. The present study will be helpful for policymakers, educationists and economists and those organizations which are working for women's progression.